Evidence for the Importance of Personalized Molecular Profiling in Pancreatic Cancer - Lili, Loukia N. (Lippincott Williams & Wilkins, 2014)
OBJECTIVES: There is a growing body of evidence that targeted gene therapy holds great promise for the future treatment of cancer. A crucial step in this therapy is the accurate identification of appropriate candidate genes/pathways for targeted treatment. One approach is to identify variant genes/pathways that are significantly enriched in groups of afflicted individuals relative to control subjects. However, if there are multiple molecular pathways to the same cancer, the molecular determinants of the disease may be heterogeneous among individuals and possibly go undetected by group analyses. METHODS: In an effort to explore this question in pancreatic cancer, we compared the most significantly differentially expressed genes/pathways between cancer and control patient samples as determined by group versus personalized analyses. RESULTS: We found little to no overlap between genes/pathways identified by gene expression profiling using group analyses relative to those identified by personalized analyses. CONCLUSIONS: Our results indicate that personalized and not group molecular profiling is the most appropriate approach for the identification of putative candidates for targeted gene therapy of pancreatic and perhaps other cancers with heterogeneous molecular etiology.